2000
DOI: 10.1136/pmj.76.896.367
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis of the small bowel in patients with AIDS

Abstract: Primary laryngeal amyloidosis is a rare benign disease of unknown aetiology. It can present with dysphonia or stridor. A woman presenting with airway compromise, who required a tracheostomy, is reported. (Postgrad Med J 2000;76:364-365) Keywords: laryngeal disease; amyloidosis Case report A 47 year old woman presented with a seven year history of dysphonia which had deteriorated recently. Fibre optic laryngoscopy showed polyps on the right false vocal cord with a suggestion of subglottic stenosis (fig 1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Bowel obstruction has been reported in a number of case reports and series. This is the fourth case of small bowel perforation due to abdominal histoplasmosis in history [6, 9, 10]. Physicians may consider histoplasmosis in the differential diagnosis of a patient with peritonitis of unknown origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…Bowel obstruction has been reported in a number of case reports and series. This is the fourth case of small bowel perforation due to abdominal histoplasmosis in history [6, 9, 10]. Physicians may consider histoplasmosis in the differential diagnosis of a patient with peritonitis of unknown origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several published cases and case series report ileal and colonic perforation. In 2000, Gumbs et al reported what they believed to be the first report of jejunal perforation [10]. A 2006 case series by Assi et al report 18 new cases of GI histoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and case series have described bowel obstruction and, rarely, perforation, the most common sites being colon or ileum [29]. Jejunal perforation has been reported only three times in our literature review [2, 10, 11]. We hereby present an HIV patient presenting with an acute abdomen found to have diffuse jejunal and mesenteric disease.…”
Section: Introductionmentioning
confidence: 85%
“…Inflammatory masses mimicking a malignancy have been described in immunosuppressed patients with colonic obstruction [10]. Small bowel obstruction with segmental strictures and ulcerations has also been reported [11]. …”
Section: Discussionmentioning
confidence: 99%